2003
DOI: 10.1046/j.1423-0410.2003.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human erythrovirus B19 DNA in healthy Belgian blood donors and correlation with specific antibodies against structural and non‐structural viral proteins

Abstract: By testing all donations as pools of 480 by un-nested PCR, and resolving positive pools to identify the responsible donations, it is possible to ensure that the viral load in fractionation pools (5000 donations) remains < 10(3) IU/ml, compatible with the efficacy of inactivation procedures and complying with Food and Drug Administration (FDA) recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
48
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 37 publications
8
48
2
3
Order By: Relevance
“…This prevalence is also similar to the data obtained in the USA (0.88 %) [8]. Nevertheless, the observed prevalence was higher compared to countries like Belgium (0.2 %) [9] and China (0.58 %) [10] and lower compared to Dutch blood donors (2.5 %) [11]. Such a difference is probably due to the different sample volume used in the B19V testing, demographic characteristics of the populations or regional specifications of the B19V circulation (genotypes) in a given geographic region.…”
supporting
confidence: 90%
“…This prevalence is also similar to the data obtained in the USA (0.88 %) [8]. Nevertheless, the observed prevalence was higher compared to countries like Belgium (0.2 %) [9] and China (0.58 %) [10] and lower compared to Dutch blood donors (2.5 %) [11]. Such a difference is probably due to the different sample volume used in the B19V testing, demographic characteristics of the populations or regional specifications of the B19V circulation (genotypes) in a given geographic region.…”
supporting
confidence: 90%
“…The results showed that 11 and 8% of the United Kingdom and Ghanaian DNA-positive donors, respectively, were IgM and IgG positive and were considered to be in the early phase of infection. These proportions were lower than those previously reported in studies performed with Belgian (28%) and French (22.2%) blood donors (2,37). This difference might simply reflect a lack of DNA detection sensitivity that artificially increased the relative proportions of samples with a high viral load, including those containing IgM.…”
Section: Discussioncontrasting
confidence: 69%
“…The prevalences observed were significantly higher than the 0.003 to 0.16% prevalences reported in previous studies (2,15,20,27,37,40,41). This discrepancy was clearly unrelated to sample origin but rather reflected differences in the sensitivity of the assays used in the different studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Although, this seems quite reassuring, these results cannot be generalized as they represent testing of small batches and continuous monitoring is recommended. Other researchers from different countries have been able to detect parvovirus B19 DNA in 1 percent of all blood cell preparations and blood products applied to the patients on a haematologic ward, in 0.9 percent of standard blood components (in 2.0 percent of pooled plasma products and in 0.7 percent of single donor products), 18 in 0.006 percent of blood donations, in 0.14 percent of single-donor blood products, 19 in 0.16 percent of plasma samples, 15 in 0.6e1.3 percent of blood donors. 13 Given these data, it is apt that screening of blood donors for parvovirus B19 is now in prospect.…”
Section: Discussionmentioning
confidence: 99%